A brief overview of targeted radionuclide therapy trials in 2022 - Healy, Aidan; Ho, Elaine; Kuo, Phillip; Zukotynski, Katherine (Frontiers in Nuclear Medicine, 2023)
There is a growing use of radionuclide therapy for the medical care of oncology patients, where radioactive pharmaceuticals are used to target and treat various cancer types. This paper provides a brief overview illustrating the spectrum of ongoing and recently completed radionuclide therapy clinical trials in oncology. The trials selected highlight the potential of radionuclide therapies to provide a promising treatment option across a spectrum of cancer patients, while also discussing the importance of patient selection and monitoring, as well as potential side effects and safety concerns. Ultimately, the results of these trials will be crucial in determining the future use of radionuclide therapies in cancer treatment.